2022
DOI: 10.1111/jfbc.14340
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 from Panax ginseng attenuates monoiodoacetate‐induced osteoarthritis by inhibiting miR ‐21‐5p/ FGF18 ‐mediated inflammation

Abstract: Osteoarthritis (OA) is a major degenerative disorder that affects the knee, and more than 33.6% of people aged over 65 years are affected by the disorder (O'Connor, 2006;Srikanth et al., 2005). The typical symptoms associated with OA include pain, swelling, stiffness, and loss of weight-bearing joint flexibility, all of which cast great burdens on patients' lives and the public health system. Currently, the most commonly used therapies for OA are those based on rehabilitation exercises and medication. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…Figures 2-4 show the potential effects of RG-RS on the canonical signaling pathways, cellular and physiological functions, and aging-related diseases, particularly the inhibition of the osteoarthritis signaling pathway where the probability of prediction is significant (−log p-value 1.7, z-score -3.2; Supplementary Table S6 and Supplementary Figure S1). That is in line with other studies of RG and RS where the potential health effect of Reg Ginseng [63][64][65][66][67] and Red Sage [68][69][70][71][72] in osteoarthritis was demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…Figures 2-4 show the potential effects of RG-RS on the canonical signaling pathways, cellular and physiological functions, and aging-related diseases, particularly the inhibition of the osteoarthritis signaling pathway where the probability of prediction is significant (−log p-value 1.7, z-score -3.2; Supplementary Table S6 and Supplementary Figure S1). That is in line with other studies of RG and RS where the potential health effect of Reg Ginseng [63][64][65][66][67] and Red Sage [68][69][70][71][72] in osteoarthritis was demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…Results of a previous study demonstrated that Rb1 enhances the expression of FGF18 by sponging miR-21-5p in MIA-induced OA rats, protecting against OA development. Overexpression of miR-21-5p abolished the chondroprotective effects of Rb1 by stimulating inflammatory responses, decreasing cell viability and attenuating FGF18-mediated chondroprotection ( 56 ) ( Table I ).…”
Section: Anti-inflammatory Properties Of Ginsenosidesmentioning
confidence: 99%
“…By self-assembly, amphiphilic ManAC4A formed nanoparticles with the passive targeting in virtue of the ELVIS effect (Extravasation through Leaky Vasculature and subsequent Inflammatory cell-mediated Sequestration) and with the active targeting to macrophage and phenotype induction capacity due to the self-assembled multivalency. By molecular recognition, the ManAC4A nanoassembly loaded Rb1, a drug effectively activating an anti-inflammatory signaling pathway, which integrated with the function of diminishing inflammation . Thus, macrocyclic therapeutics and macrocyclic delivery were merged, attributable to the functionalized design of the macrocyclic host and the efficient recognition between host and guest drugs.…”
Section: Introductionmentioning
confidence: 99%
“…By molecular recognition, the ManAC4A nanoassembly loaded Rb1, a drug effectively activating an anti-inflammatory signaling pathway, which integrated with the function of diminishing inflammation. 55 Thus, macrocyclic therapeutics and macrocyclic delivery were merged, attributable to the functionalized design of the macrocyclic host and the efficient recognition between host and guest drugs. Collectively, the Rb1@ManAC4A nanoassembly, just containing two components, integrated triple targeting including ELVIS targeting, macrophagetargeting and hypoxia-targeted release, and triple therapy including ROS scavenging, macrophage polarization, and the anti-inflammatory effect of Rb1, which was reasonably applied in synergistic anti-inflammatory therapy on RA rats (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%